CD44 variant‐dependent redox status regulation in liver fluke‐associated cholangiocarcinoma: A target for cholangiocarcinoma treatment. Issue 7 (20th June 2016) - Thanee, Malinee; Loilome, Watcharin; Techasen, Anchalee; Sugihara, Eiji; Okazaki, Shogo; Abe, Shinya; Ueda, Shiho; Masuko, Takashi; Namwat, Nisana; Khuntikeo, Narong; Titapun, Attapol; Pairojkul, Chawalit; et al.
Abstract : Expression of CD44, especially the variant isoforms (CD44v) of this major cancer stem cell marker, contributes to reactive oxygen species (ROS) defense through stabilizing xCT (a cystine–glutamate transporter) and promoting glutathione synthesis. This enhances cancer development and increases chemotherapy resistance. We investigate the role of CD44v in the regulation of the ROS defense system in cholangiocarcinoma (CCA). Immunohistochemical staining of CD44v and p38 MAPK (a major ROS target) expression in Opisthorchis viverrini ‐induced hamster CCA tissues (at 60, 90, 120, and 180 days) reveals a decreased phospho‐p38 MAPK signal, whereas the CD44v signal was increased during bile duct transformation. Patients with CCA showed CD44v overexpression and negative‐phospho‐p38 MAPK patients a significantly shorter survival rate than the low CD44v signal and positive‐phospho‐p38 MAPK patients ( P = 0.030). Knockdown of CD44 showed that xCT and glutathione levels were decreased, leading to a high level of ROS. We examined xCT‐targeted CD44v cancer stem cell therapy using sulfasalazine. Glutathione decreased and ROS increased after the treatment, leading to inhibition of cell proliferation and induction of cell death. Thus, the accumulation of CD44v leads to the suppression of p38 MAPK in transforming bile duct cells. The redox status regulation of CCA cells depends on the expression of CD44v to contribute the xCT function and is a link to the poor prognosis of patients. Thus, an xCT inhibitor could inhibit cell growth and activate cell death. This suggests that an xCT‐targeting drug may improve CCA therapy by sensitization to the available drug (e.g. gemcitabine) by blocking the mechanism of the cell's ROS defensive system. Abstract : The redox status regulation of CCA cells depends on the expression of CD44v to contribute the xCT function and is a link to the carcinogenesis and poor prognosis of patients.